Application of molecular simulations: Insight into liquid bridging and jetting phenomena - Nezbeda, I.; Jirsák, J.; Moučka, F.; Smith, W.R. (Condensed Matter Physics, 2015)
Molecular dynamics simulations have been performed on pure liquid water, aqueous solutions of sodium chloride, and polymer solutions exposed to a strong external electric field with the goal to gain molecular insight into the structural response to the field. Several simulation methodologies have been used to elucidate the molecular mechanisms of the processes leading to the formation of liquid bridges and jets (in the production of nanofibers). It is shown that in the established nanoscale structures, the molecules form a chain with their dipole moments oriented parallel to the applied field throughout the entire sample volume. The presence of ions may disturb this structure leading to its ultimate disintegration into droplets; the concentration dependence of the threshold field required to stabilize a liquid column has been determined. Conformational changes of the polymer in the jetting process have also been observed.